Melding kin structure and demography to elucidate source and sink habitats in fragmented landscapes - J. C. Beasley; G. Dharmarajan; O. E. Rhodes Jr. (Ecosphere, 2015)
The source‐sink model undoubtedly is one of the most established paradigms for associating variance in population dynamics with heterogeneity in habitat quality. However, despite extensive theoretical support by the scientific community, the majority of studies seeking empirical validation for this model have lacked sufficient data to distinguish source and sink habitats, particularly for large or secretive mammals. Using relatively long‐term mark‐recapture and genetic data for a generalist mesopredator within a fragmented agricultural ecosystem, we show that use of a two‐stage approach incorporating both genetic and demographic data can be a powerful tool for evaluating the population structure of organisms occupying complex ecological systems. We further demonstrate that a strong concordance exists between demographic attributes and underlying genetic expectations, suggesting evaluation of fine‐scale genetic patterns alone may provide valuable insights into the population dynamics of species. These data have important implications for advancing our ability to quantify heterogeneity in population stability, particularly for large or imperiled species where sufficient demographic data cannot be obtained to parameterize traditional source‐sink models.